2017
DOI: 10.3399/bjgp16x688417
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of GPs when using an early-intervention decision support system: a high-fidelity simulation

Abstract: BackgroundObservational and experimental studies of the diagnostic task have demonstrated the importance of the first hypotheses that come to mind for accurate diagnosis. A prototype decision support system (DSS) designed to support GPs’ first impressions has been integrated with a commercial electronic health record (EHR) system.AimTo evaluate the prototype DSS in a high-fidelity simulation.Design and settingWithin-participant design: 34 GPs consulted with six standardised patients (actors) using their usual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 22 publications
2
69
0
1
Order By: Relevance
“…A review of the field indicates the potential for decision support systems (DSSs) to provide tailored differential diagnoses . For example, in one simulation, a computerised DSS led to an 8–9% improvement in diagnostic accuracy . Because ID is attached to a leading option, ideally interventions should target an early stage of a consultation before physicians have engaged in any hypothesis generation .…”
Section: Implications For Health Professionalsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the field indicates the potential for decision support systems (DSSs) to provide tailored differential diagnoses . For example, in one simulation, a computerised DSS led to an 8–9% improvement in diagnostic accuracy . Because ID is attached to a leading option, ideally interventions should target an early stage of a consultation before physicians have engaged in any hypothesis generation .…”
Section: Implications For Health Professionalsmentioning
confidence: 99%
“…62 For example, in one simulation, a computerised DSS led to an 8-9% improvement in diagnostic accuracy. 63 Because ID is attached to a leading option, ideally interventions should target an early stage of a consultation before physicians have engaged in any hypothesis generation. 64 Two studies confirm that, compared to later stages of a diagnosis, computerised DSS intervention was most effective early in the diagnostic process before physicians started gathering information.…”
Section: Implications For Health Professionalsmentioning
confidence: 99%
“…Developing new codes to denote diagnostic uncertainty in the patient‐provider encounter could be one possible way of ensuring that diagnostic uncertainty is appropriately captured in the medical record . Using separate coding systems for diagnosis (eg, ICD‐10) and reason for encounter (eg, SNOMED CT) within a linked Episode of Care could also be explored as it can allow the diagnosis to evolve over time accounting for uncertainty . Improvements in current EHR systems and coding terminologies to “code” diagnostic uncertainty in the medical record as “structured data” may also be explored .…”
Section: Discussionmentioning
confidence: 99%
“…First, a retrospective diabetes clinical‐genomic study, which demonstrated that linked genomic and clinical data, could be used across several countries using the same platform. Second, a diagnostic decision support system in case of chest pain, abdominal pain, and shortness of breath, which demonstrated that giving early prompts of diagnosis to clinicians was more favorable than giving late prompts . Third, a prospective acid reflux clinical study, an international RCT evaluating dosing regimen of proton pumps inhibitors (medication used for gastric reflux) on multiple sites .…”
Section: The Transform Experiencementioning
confidence: 99%
“…Second, a diagnostic decision support system in case of chest pain, abdominal pain, and shortness of breath, 28 which demonstrated that giving early prompts of diagnosis to clinicians was more favorable than giving late prompts. 29 The framework described above can address the challenges mentioned earlier in knowledge production, transfer, and application.…”
Section: Applicationsmentioning
confidence: 99%